2021
DOI: 10.1016/j.jhep.2021.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Non-epidemic HCV genotypes in low- and middle-income countries and the risk of resistance to current direct-acting antiviral regimens

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 50 publications
1
31
0
1
Order By: Relevance
“…In vitro studies showed that 30K and 31M RAS conferred high levels of resistance to NS5A inhibitors. 31,32 It was reported that in mainland China, 96% of genotype 3b isolates carried the RAS combination A30K + L31M, 33 and a Dutch nationwide cohort study showed all genotype 3b patients had 30K and 31M RAS, which were associated with a lower SVR (63%). 34 Y93H was the most prevalent RAS at the end of treatment and was detected in 71.4% of non-SVR patients (Figure 3B).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that 30K and 31M RAS conferred high levels of resistance to NS5A inhibitors. 31,32 It was reported that in mainland China, 96% of genotype 3b isolates carried the RAS combination A30K + L31M, 33 and a Dutch nationwide cohort study showed all genotype 3b patients had 30K and 31M RAS, which were associated with a lower SVR (63%). 34 Y93H was the most prevalent RAS at the end of treatment and was detected in 71.4% of non-SVR patients (Figure 3B).…”
Section: Discussionmentioning
confidence: 99%
“…Within our cohort there are six countries which report unusual subtypes among their patient population. Unusual subtypes are more challenging to treat as SVR rates tend to be lower potentially due to the natural variation at baseline of these subtypes [12,33,34]. Countries where these unusual subtypes are highly prevalent among the countries with the highest HCV prevalence in the world [11].…”
Section: Discussionmentioning
confidence: 99%
“…HCV harbors a 10 kb-long RNA genome which displays a high level of genetic variation due to the lack of a proof-reading activity of its RNA-dependent RNA polymerase enzyme, resulting in the emergence of different HCV genotypes and subtypes across the globe [ 4 ]. So far, at least six (6) genotypes of HCV have been identified, with multiple subtypes [ 5 ]. Different HCV genotypes are prevalent in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypes 1 and 3 are the two most common genotypes of HCV [ 6 , 7 ]. Genotypes 2, 3, 4, 5, and 6 are found predominantly in West Africa and Americas, the Indian sub-continent and Southeast Asia, Central and East Africa, South Africa, and Southeast Asia, respectively [ 5 ].…”
Section: Introductionmentioning
confidence: 99%